If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -39 = x + -62 Reorder the terms: -39 = -62 + x Solving -39 = -62 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -39 + -1x = -62 + x + -1x Combine like terms: x + -1x = 0 -39 + -1x = -62 + 0 -39 + -1x = -62 Add '39' to each side of the equation. -39 + 39 + -1x = -62 + 39 Combine like terms: -39 + 39 = 0 0 + -1x = -62 + 39 -1x = -62 + 39 Combine like terms: -62 + 39 = -23 -1x = -23 Divide each side by '-1'. x = 23 Simplifying x = 23
| 3-5(2+4x)=5 | | 12x-5=5x+23 | | 2x^2-x^2+1-4=0 | | 4cos^2x-3cosx=0 | | 5(a-12)-24=3(a+2) | | 2x^3-5x-69=0 | | 1.3(x+2)+5.6=17.3 | | x-3=-.5x+3 | | 5-9x=-4x | | 3z-2z+8= | | 3x+9=-1Y+29 | | 2x^3-5x-9=0 | | 12-42=3(x-2)-9 | | 100=33+x | | 15=(5k-13) | | 2x^2=1080 | | 32y^2+5y+6y= | | 40=-8(x+7) | | 700=84+28d | | -3(r+8)=48 | | 2x=250+x | | -15x+32=x | | 15w-19w=24 | | .5y-1=.33 | | -(3x+4)+15=6-4x | | (6-4)(6+3)=18 | | 37-13=4(x-6) | | 38=-1X | | y=3x+(2x-1) | | 40x+x^2=624 | | 7(2*-3)+3=24 | | 90+51=2x+1 |